General isochronous rhythm in echolocation calls and social vocalizations of the bat Saccopteryx bilineata. Issue 1 (2nd January 2019) - Burchardt, Lara S.; Norton, Philipp; Behr, Oliver; Scharff, Constance; Knörnschild, Mirjam
Abstract : Rhythm is an essential component of human speech and music but very little is known about its evolutionary origin and its distribution in animal vocalizations. We found a regular rhythm in three multisyllabic vocalization types (echolocation call sequences, male territorial songs and pup isolation calls) of the neotropical bat Saccopteryx bilineata . The intervals between element onsets were used to fit the rhythm for each individual. For echolocation call sequences, we expected rhythm frequencies around 6–24 Hz, corresponding to the wingbeat in S. bilineata which is strongly coupled to echolocation calls during flight. Surprisingly, we found rhythm frequencies between 6 and 24 Hz not only for echolocation sequences but also for social vocalizations, e.g. male territorial songs and pup isolation calls, which were emitted while bats were stationary. Fourier analysis of element onsets confirmed an isochronous rhythm across individuals and vocalization types. We speculate that attentional tuning to the rhythms of echolocation calls on the receivers' side might make the production of equally steady rhythmic social vocalizations beneficial.